Dendritic Cells Reveal a Broad Range of MHC Class I Epitopes for HIV-1 in Persons with Suppressed Viral Load on Antiretroviral Therapy - Huang, Xiao-Li (Public Library of Science, 2010)
BACKGROUND: HIV-1 remains sequestered during antiretroviral therapy (ART) and can resume high-level replication upon cessation of ART or development of drug resistance. Reactivity of memory CD8(+) T lymphocytes to HIV-1 could potentially inhibit this residual viral replication, but is largely muted by ART in relation to suppression of viral antigen burden. Dendritic cells (DC) are important for MHC class I processing and presentation of peptide epitopes to memory CD8(+) T cells, and could potentially be targeted to activate memory CD8(+) T cells to a broad array of HIV-1 epitopes during ART. PRINCIPAL FINDINGS: We show for the first time that HIV-1 peptide-loaded, CD40L-matured DC from HIV-1 infected persons on ART induce IFN gamma production by CD8(+) T cells specific for a much broader range and magnitude of Gag and Nef epitopes than do peptides without DC. The DC also reveal novel, MHC class I restricted, Gag and Nef epitopes that are able to induce polyfunctional T cells producing various combinations of IFN gamma, interleukin 2, tumor necrosis factor alpha, macrophage inhibitory protein 1 beta and the cytotoxic de-granulation molecule CD107a. SIGNIFICANCE: There is an underlying, broad antigenic spectrum of anti-HIV-1, memory CD8(+) T cell reactivity in persons on ART that is revealed by DC. This supports the use of DC-based immunotherapy for HIV-1 infection.